A violência escolar na relação professor-aluno: vozes de professoras da educação infantil - Costa, Samuel Almeida (Brasil, 2024)
School violence is a worrying and recurring topic in everyday schools that can impact children's emotional, intellectual development and learning. Thus, this study's main objective is to understand how school violence in the teacher-student relationship impacts the learning of preschool children at a Children's Educational Center in Parintins, AM. In this way, we sought to identify which forms of school violence are recurrent in the teacher-student relationship and their possible causes; verify the actions and strategies used by the CEI to combat this phenomenon, considering the challenges and possibilities for overcoming it and analyzing the impacts of school violence on the emotional relationship between teacher and students, as well as on children's learning. The study takes a qualitative approach, consisting of descriptive research, whose data production occurred through semi-structured interviews with the manager, two teachers and classroom observation. The results reveal that school violence is something recurrent within the institution and in a way it is a practice that has become naturalized due to the frequency with which it occurs. Despite having basic knowledge on the subject, violence is still a difficult subject to discuss, especially when it involves children, which is why it is understood by teachers as “children's things. It is concluded that these results point to the need for investment in strategies that prevent school violence in the teacher-student relationship, bringing the family closer to the school, given the importance of the partnership between these two institutions, aiming to improve coexistence in the space school and, consequently, promoting the quality of education for young children.